2017
DOI: 10.17707/agricultforest.63.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Results of Investigations of Genotype and Its Influence on the Yield, Quality and Economic Effect of Virginia Tobacco in R. Macedonia

Abstract: SUMMARYInvestigations were carried out in 2014 and 2015 on the experimental field of the Scientific Tobacco Institute -Prilep. They included four introduced fertile varieties and three domestic promising hybrid lines in CMS form created in the Institute, with the standard Australian variety Ca-757 used as a check. The trial was set up in randomized blocks with 4 replications. The highest average yield per stalk (161,7 g) and per hectare (3 593 kg) was achieved in line V-79/09 CMS F 1 . The lowest yield per sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The average yield value obtained from the five-year results is 3450 kg/ha, which puts this line in the group of high-yielded genotypes Risteski et al (2012). reported that male-sterile genotypes of Virginia tobacco created in the Scientific Tobacco Institute -Prilep had a yield of 3549 kg/ha (line V-53 CMS F1) Devčid et al (1982).…”
mentioning
confidence: 92%
“…The average yield value obtained from the five-year results is 3450 kg/ha, which puts this line in the group of high-yielded genotypes Risteski et al (2012). reported that male-sterile genotypes of Virginia tobacco created in the Scientific Tobacco Institute -Prilep had a yield of 3549 kg/ha (line V-53 CMS F1) Devčid et al (1982).…”
mentioning
confidence: 92%